Fatigue Life Behaviour Of Fiberglass Reinforced Composites Subjected To Constant And Variable Amplitude Loadings - Jimit, Roy Hanson (2019)
This study focuses on the variable amplitude loadings effect on fatigue life behaviour of Fiberglass-reinforced composite (FGRC). Unidirectional fiberglass-reinforced composite were used as subjects of this study due to their wide application in automotive and engineering components. The manufacturing some of automotive parts are made from fiberglass including the interior or exterior panels, dashboard components, seats, spoilers, sills panel and body structures. The study of fatigue life under variable amplitude loadings (VAL) is an important subject as most of engineering components are subject to stresses which vary with time. Fatigue failure usually occurred without warning. Therefore, the needs of more predictive tools and understanding on the integrity of this material could help to produce a more reliable engineering material in the future. The main objective of this study is to investigate the effect of overloads (OL) and underloads (UL) toward the fatigue life behaviour of the FGRC test coupon of different orientation which are [0/90]° and [±45]° orientations and chopped strand mat (CSM). Firstly, a static finite element analysis was performed to determine the most critical area of the FGRC test coupon. Next, the critical stress value was recorded from the tensile test on the test coupon according to the standard in ASTM D3039. Tensile test is carried out to determine the mechanical properties of the FGRC. The results showed that the Ultimate Tensile Stress (UTS) of FGRC is the highest in [0/90]° orientations compared to [±45]° orientation and CSM. After that the fatigue tests were carried out at room temperature in accordance to the ASTM D3479 for both Constant Amplitude Loadings (CAL) and Variable Amplitude Loadings (VAL). Secondly, the CAL fatigue test is carried out for all the orientations including CSM. Results showed [0/90]° orientations have the highest fatigue life cycle. Thirdly, OL and UL effects were generated from the CAL fatigue test results. Results showed that UL effect deteriorate the fatigue life behaviour of FGRC from 1.4% to 14% decrement from the actual value when being compared to result in CAL due to acceleration effect in fatigue crack growth rate while the effect of OL increase the fatigue life behaviour of FGRC by minimum 5% from the actual value due to retardation effect in the fatigue crack growth rate.